Elucidating structure and dynamics of crystalline α‐zirconium phosphates intercalated with water and methanol by multinuclear solid‐state MAS NMR: A comprehensive NMR approach. (7th March 2022) - Bakhmutov, Vladimir I.; Contreras‐Ramirez, Aida; Drake, Hannah; Zhou, Hong‐Cai
Abstract: Solid‐state NMR experiments on 2 H, 31 P, 13 C, and 1 H nuclei, including 31 P T1, 1 H T1, and 1 H T1ρ measurements, as well as on the kinetics of proton‐phosphorus cross‐polarization have been performed to characterize the crystalline and amorphous α‐zirconium phosphates, which were intercalated with D2 O and/or CD3 OD. The 13 C{ 1 H} CP MAS NMR experiment performed for compound 1‐CD 3 OD (Zr (HPO4 )2 . 0.2CD3 OD) with carbon cross‐polarization via protons of phosphate groups has provided a prove that the methanol was intercalated into the interlayer spaces of this compound. The variable‐temperature 2 H solid‐echo MAS NMR spectra of intercalated compounds demonstrated that the methanol molecules, in contrast to the mobile water, were immobile, keeping, however, free CD3 rotations around the C3 ‐axis. It has been demonstrated that the intercalated species, D2 O and CD3 OD, do not affect the high‐frequency motions of the phosphate groups. By utilizing local structural models that satisfy the constraints of the experimental data, it has been suggested that the immobile methanol molecules are located in the cavity between two neighboring layers of the zirconium phosphates. Thus, the present work illustrates the reliable criteria in a comprehensive NMR approach to structural and dynamic studies of such systems. Abstract : The following local structural model has been generated to satisfy all the experimental data. In this model, the immobile methanol molecules are located within a cavity between two layers of the zirconium phosphates.